Envolvimento dos biomarcadores endoteliais e fatores de risco ateroscleróticos e sua correlação com o espessamento médiointimal carotídeo - Pereira, Lianna Cavalcante (2018)
Cardiovascular diseases are the major cause of morbidity and mortality worldwide. Atherosclerosis is a chronic condition with immunoinflammatory involvement that can trigger stroke or coronary diseases and acute myocardial infarction. Some surviving patients may present sequelae with prolonged hospitalization and high cost for the public health system and social security. Carotid mode B ultrasonography can be an important method to endothelial analysis in order to identify atherosclerotic risk. This work evaluated the association of endothelial function biomarkers (ICAM-1, VCAM-1, syndecan-1) to atherosclerotic risk factors and carotid intima-media thickness (IMT). Seventy-one patients from Dental Specialty Centers (CEOs) were recruited, who underwent routine evaluation in Fortaleza/CE from 2014 to 2017. Sociodemographic, nutritional and anthropometric profiles were evaluated, as well as laboratory tests and ultrasound evaluation. The laboratory exams included were: hematological, biochemical analysis (lipid fractions, liver and renal functions). Atherogenic indices, including Castelli 1 and Castelli 2, and plasma atherogenic index (AIP) were calculated. Endothelial biomarkers’ serum evaluation was performed by enzyme-linked immunosorbent assay (ELISA). Anthropometric measurements consisted of measures of weight, height, arm (AC), waist (WC) and abdomen (ABC) circumferences, waist hip ratio (WHR), skinfolds, and body mass index (BMI). The population studied had a mean age of 45.3 years, most of them women (84.5%). The population was overweight. There was no change in the other anthropometric measures. Around 31,9% of patients showed atheroma plates in the common carotid arteries. In the total population, the mean values of total cholesterol were at the borderline level for more (204.1 ± 45.7 mg/dL). A positive and significant correlation between ICAM-1 and VCAM-1 was found regardless of age and BMI. Patients older than 45 years and BMI> 25 presented a positive and significant correlation of AC, WC and WHR with ICAM-I levels. In the total population, ICAM-1 levels correlated positively and significantly with glycaemia, VLDL, triglycerides, Castelli 1, IAP, AST and ALT. In individuals aged less than 45 years and BMI> 25, ICAM-1 levels showed a positive correlation with serum levels of VLDL, triglycerides, AST, ALT, albumin and the indices of Castelli 1 and IAP. HDL levels correlated negatively with ICAM-1 levels. In the total population, serum levels of VCAM-1 correlated negatively with LDL. In addition, in patients younger than 45 years, serum VCAM-1 levels correlated negatively with IMT in the right common carotid artery. In the total population, the serum levels of syndecan-1 were inversely correlated with blood total proteins. No significant correlation was identified with the other variables studied. In addition, no correlation was observed between C-reactive protein levels and the serum endothelial biomarkers. Thus, our results suggest that biomarkers of endothelial function, especially serum levels of ICAM-1, have significant correlations with atherosclerotic risk factors in this population. This work may guide possible early intervention measures aimed at the prevention of atherosclerotic cardiovascular diseases. More studies with a greater number of subjects are necessary to better evaluate these findings.